(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the principles of instilling religious tolerance in the minds of young people in the era of globalization from a religious and secular perspective. The ideas of religious tolerance in the era of globalization are studied based on the works and wise words of Sufi figures Ahmad Yassavi, Alisher Navoi, Imam Bukhari. The secrets of the virtual world called “Digital Silk Road” are revealed. The scientific and philosophical conclusions of the theory of inicos are presented.